Exploration and mitigation of gender bias in word embeddings from transformer-based language models - Hossain, Ariyan; Haque, Rakinul; Hannan, Khondokar Mohammad Ahanaf; Rafa, Nowreen Tarannum; Musarrat, Humayra (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.